Menguraikan Materi Kompleks: Peran Explainer Video serta Tantangan dan Solusinya di Universitas - Walidaroyani, Ainia; Ahsan, Moh (jurnal ABDIMAS Indonesia, 2024)
Indonesia's digital literacy rate has increased significantly until 2023. With the growth of technology and the internet becoming more widespread across the country, more Indonesians are starting to actively engage in digital platforms. The relationship between increasing digital literacy and gadget usage trends in Indonesia is closely linked. Along with the development of digital technology and the availability of various online content, gadget usage is increasing to access various types of content, such as videos, music, games and social media. These contents have different appeals and fulfill users' entertainment, information and social interaction needs. The challenge of using explainer videos as an explanatory tool in Indonesian society is the complexity of conveying effective information. While animated videos have the potential to convey ideas and concepts in an engaging and easy-to-understand way, there are several barriers to overcome. One of them is the difficulty in simplifying complex content into a short and clear animation format. In addition, the different levels of digital literacy and accessibility to technology in different walks of life also pose obstacles to the dissemination and acceptance of animated videos as an effective explanatory tool.